2000
DOI: 10.1016/s1388-1981(00)00054-8
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid transport in eukaryotic cells

Abstract: Sphingolipids constitute a sizeable fraction of the membrane lipids in all eukaryotes and are indispensable for eukaryotic life. First of all, the involvement of sphingolipids in organizing the lateral domain structure of membranes appears essential for processes like protein sorting and membrane signaling. In addition, recognition events between complex glycosphingolipids and glycoproteins are thought to be required for tissue differentiation in higher eukaryotes and for other specific cell interactions. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
94
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 301 publications
(200 reference statements)
1
94
0
1
Order By: Relevance
“…Although mammalian SLs are known to reside mainly in the exoplasmic leaflet of the plasma membrane (Holthuis et al, 2001), ϳ20% of them are found in the cytoplasmic leaflet (Boon and Smith, 2002). Even if no data are currently available about the distribution of SLs over the two leaflets of the yeast plasma membrane (van Meer and Holthuis, 2000), it is thus conceivable that at least a small fraction of these lipids face the cytoplasm, in particular if they are forming a shell around transmembrane proteins. Because the cytosolic lysines 76, 87, and 91 of Gap1 are close to the membrane ( Figure 3F), they might be part of the region containing the SL head groups and thus be inaccessible to posttranslational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Although mammalian SLs are known to reside mainly in the exoplasmic leaflet of the plasma membrane (Holthuis et al, 2001), ϳ20% of them are found in the cytoplasmic leaflet (Boon and Smith, 2002). Even if no data are currently available about the distribution of SLs over the two leaflets of the yeast plasma membrane (van Meer and Holthuis, 2000), it is thus conceivable that at least a small fraction of these lipids face the cytoplasm, in particular if they are forming a shell around transmembrane proteins. Because the cytosolic lysines 76, 87, and 91 of Gap1 are close to the membrane ( Figure 3F), they might be part of the region containing the SL head groups and thus be inaccessible to posttranslational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Arv1p may function within one or both of these pathways in the ER-toGolgi transport of ceramide. Because ceramide is synthesized in the ER of animal cells and is transported to the Golgi for conversion to sphingomyelin (65), hArv1p may function in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the transportation of sphingolipids from one organelle to others must be highly organized. The interorganelle trafficking of sphingolipids is mediated in either a vesicular or nonvesicular manner (2). For instance, in mammalian cells, a de novo synthesized ceramide in ER membranes is transported to the Golgi in a nonvesicular manner by an ER-to-Golgi specific ceramide transporter (CERT, also known as GPBP⌬26, a splicing variant of Goodpasture antigenbinding protein) (3,4).…”
mentioning
confidence: 99%